The garb of being : embodiment and the pursuit of holiness in late ancient Christianity - Frank, Georgia, 1963-; Holman, Susan R.; Jacobs, Andrew S., 1973- (Orthodox Christianity and contemporary thought., 2020)
This collection of essays explores how the body became a touchstone for late antique practice and religious imagination through stories from the eastern Christian world of antiquity: monks and martyrs, families and congregations, and textual bodies from antiquity subject to modern interpretations.